4.2q-5.9-5.5q=-2.3q-3.6

Simple and best practice solution for 4.2q-5.9-5.5q=-2.3q-3.6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4.2q-5.9-5.5q=-2.3q-3.6 equation:


Simplifying
4.2q + -5.9 + -5.5q = -2.3q + -3.6

Reorder the terms:
-5.9 + 4.2q + -5.5q = -2.3q + -3.6

Combine like terms: 4.2q + -5.5q = -1.3q
-5.9 + -1.3q = -2.3q + -3.6

Reorder the terms:
-5.9 + -1.3q = -3.6 + -2.3q

Solving
-5.9 + -1.3q = -3.6 + -2.3q

Solving for variable 'q'.

Move all terms containing q to the left, all other terms to the right.

Add '2.3q' to each side of the equation.
-5.9 + -1.3q + 2.3q = -3.6 + -2.3q + 2.3q

Combine like terms: -1.3q + 2.3q = 1q
-5.9 + 1q = -3.6 + -2.3q + 2.3q

Combine like terms: -2.3q + 2.3q = 0.0
-5.9 + 1q = -3.6 + 0.0
-5.9 + 1q = -3.6

Add '5.9' to each side of the equation.
-5.9 + 5.9 + 1q = -3.6 + 5.9

Combine like terms: -5.9 + 5.9 = 0.0
0.0 + 1q = -3.6 + 5.9
1q = -3.6 + 5.9

Combine like terms: -3.6 + 5.9 = 2.3
1q = 2.3

Divide each side by '1'.
q = 2.3

Simplifying
q = 2.3

See similar equations:

| 8p=2(p+9) | | 8(w-2)= | | 100.39=28.90+49.99+2x | | (2x+5)+(x-2)= | | a+(a+450000)=625000000 | | 38.5=2x-1.5+2x-1.5+x+x+x+7.2 | | 33.9ab-82.4ac+29.3ad-84.8ac+73.2ab= | | y-17=-33 | | 2x-20=36.37 | | 9.9x+38.57=-10.1+38.41b | | 108=x+x+3.5x+3.5x | | Y^2+2y-24=0 | | 66.8=2x+4.7+2x+4.7+2x+4.7+2x+4.7 | | (c-3)(c-3)=o | | x+4=9x-72 | | 9(3+x)= | | 27y^2-52y+25= | | 66.8=2x+4.7 | | 5p-(4p-4)=17 | | 19.8=x+2.9+4.5+x | | 9.9x+38.57=-10.1+38.41 | | 15(x+1)=5(4x) | | y=zr | | p=0.4+-350.002x | | 2w^9-20w^8-48w^7= | | p=1.4+-350x-1+-0.002x | | 1(t-4)+7t=4(2t+3)-8 | | 15x+15=20x | | p(x)=-0.002x^2+1.4x-350 | | 7.4x-2.9=11.9 | | 1.95x-4.38z+2.83a-5.21z-9.27x= | | v+(v-16)+3(30-v)=641 |

Equations solver categories